Microsoft Cambridge at TREC 2003: HARD track - Robertson, Stephen; Zaragoza, H.; Taylor, Mike (The Twelfth Text REtrieval Conference, TREC 2003, 2004)
Portions of these proceedings are available in either PS and/or PDF formats. Papers need to be saved before viewing in the appropriate software. For additional information on these utilities, please reference the [help] file. The inclusion or omission of a particular company or product implies neither endorsement nor criticism by NIST. Any opinions, findings, and conclusions or recommendations expressed in the individual papers are the authors' own and do not necessarily reflect those of the sponsors.